Characterization of nanograined powder samples using the Rietveld method applied to electron diffraction ring patterns. (12th April 2017) - Serafini, A.; Lutterotti, L.; Gross, S.; Gialanella, S.
Abstract : A full-pattern fitting procedure based on the Rietveld method was applied to electron diffraction ring patterns of a two-phase system, exhibiting the co-presence of zinc sulfide (sphalerite) and zinc oxide (Wurtzite). Bright and dark field (DF) images reveal the presence of micrometric aggregates, composed of quasi-spherical nanosized crystallites. These conventional transmission electron microscopy imaging methods provide a general morphological characterization of the specimens although, in the present case, they are not suitable for a detailed characterization of the microstructural features of the analyzed samples. Owing to the overlap and broadening of the diffraction rings of the two phases, DF images cannot provide a satisfactory picture of the individual crystallites of each single phase. To overcome this limit, the mentioned Rietveld approach was applied to model the electron diffraction data. The crystalline domain size and relevant shapes for both phases were successfully evaluated using the proposed methodological approach. The excellent results obtained in the microstructural characterization of the nanostructured multiphase samples demonstrate the capability of this technique, that may represents a fully quantitative method for the routine characterization of crystalline nanomaterials.